Model checking the behavior of frameworks extended with other frameworks - Balaguer, Federico (2005)
Frameworks are important in software development. There are problematic aspects of framework development. When frameworks are extended with functionality implemented by other frameworks, developers face a difficult task solving static and (specially) dynamic mismatches. The dynamic aspect is less visible to developers thus it is usually the cause of failure, specially in frameworks using multi threading pro- gramming. This paper shows how to verify the soundness of frame- work compositions at dynamic level using using temporal logic and tools provided by Full Maude.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Conference on Object Oriented Programming, Systems, Languages, and Applications (20ma : 2005 oct. 16-20 : San Diego, California). Proceedings. ACM : Nueva York, 2005, pp. 122-123
Keywords: DESARROLLO DE SOFTWARE; DISEÑO DE FRAMEWORKS; VERIFICACIÓN DE PROGRAMAS